ECHO‐CT: An Interdisciplinary Videoconference Model for Identifying Potential Postdischarge Transition‐of‐Care Events. Issue 2 (20th January 2021) - Gonzalez, Mariana R; Junge‐Maughan, Lauren; Lipsitz, Lewis A; Moore, Amber
Abstract : BACKGROUND: Discharge from the hospital to a post–acute care setting can be complex and potentially dangerous, with opportunities for errors and lapses in communication between providers. Data collected through the Extension for Community Health Outcomes–Care Transitions (ECHO‐CT) model were used to identify and classify transition‐of‐care events (TCEs). METHODS: The ECHO‐CT model employs multidisciplinary videoconferences between a hospital‐based team and providers in post–acute care settings; during these conferences, concerns regarding the patient's care transition were identified and recorded. The videoconferences took place from January 2016 to October 2018 and included patients discharged from inpatient medical and surgical services to a total of eight participating post–acute care facilities (skilled nursing facilities or long‐term acute care hospitals). RESULTS: During the interdisciplinary videoconferences in this period, 675 patients were discussed. A total of 139 TCEs were identified; 58 (41.7%) involved discharge communication or coordination errors and 52 (37.4%) were classified as medication issues. CONCLUSION: The TCEs identified in this study highlight areas in which providers can work to reduce issues arising during the course of discharge to post–acute care facilities. Standardized processes to identify, record, and report TCEs are necessary to provide high‐quality, safe care for patients as they move across care settings.